Thrombolytic treatment of simultaneous pulmonary embolism and impending paradoxical embolism through a patent foramen ovale: a different thrombolytic regimen. - Turfan, Murat; Vatankulu, Mehmet Akif; Murat, Sani Namik; Oksuz, Fatih; Duran, Mustafa; Ornek, Ender (My University, 2012)
A 72 year-old woman was admitted with a one-week history of weakness, right limb pain and progressive breathlessness. Her blood pressure was 60/40 mmHg, ECG showed inverted T waves in the precordial leads and incomplete right bundle branch block (RBBB). Transthoracic echocardiography revealed a large serpentine mobile mass across the atrial septum and mitrale valve extending into the left ventricular cavity. The right ventricle was dilated and peak systolic tricuspid annular velocity (RV-Sm) was 6.5 cm/sn, indicate right ventricular systolic function was severely depressed. Transoesophageal echocardiography showed a large, mobile thrombus in the foramen ovale, extending into the left atrium and ventricle. As the patient was in a haemodynamically compromised condition, high dose rapid infusion of streptokinase was administered. However, the thrombus did not fully resolve with this intervention. Therefore, low dose continuous streptokinase infusion was administered for an additional 72 h resulting in full resolution of the lesion by the third day of therapy. The optimal management of impending paradoxical embolism remains unclear. Prolonged continuous thrombolytic infusion may be a option for patients who do not experience full resolution of high risk thrombi with conventional thrombolytic therapy.